Bribery: Behavioral Drivers of Distorted Decisions. Issue 3 (24th November 2018) - Gneezy, Uri; Saccardo, Silvia; van Veldhuizen, Roel
Abstract: We experimentally investigate behavioral drivers of bribery, focusing on the role of self-interest, reciprocity, and moral costs associated with distorting judgment. In our laboratory experiment, two participants compete for a prize; a referee picks the winner. Participants can bribe the referee. When the referee can keep only the winner's bribe, bribes distort her judgment. When the referee keeps the bribes regardless of the winner, bribes no longer influence her decision. An experiment in an Indian market confirms these results. These findings imply that our participants are influenced by bribes out of self-interest, and not because of a desire to reciprocate. Further evidence shows that self-interest guides decisions to a greater extent when referees have scope for avoiding the moral costs associated with distorting judgment. As a result, limiting referees' ability to form self-serving evaluations can significantly reduce the effectiveness of bribes.